Pengaruh Penggunaan Serbuk Biji Kelor Terhadap Jumlah Escherichia coli Pada Air Sumur Gali - Ruli Kusuma Wigati; Lucky Herawati; Bambang Suwerda (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
Dug well water which are contaminated by E. coli are not safe for drinking purposes, so that need proper treatment. However, in long term, the use of chemical compound as water purifier may lead to unwanted effect and therefore the natural ones is more preferable. This study was aimed to understand the applicability of Kelor (Moringa oliefera) seed powder in reducing the number ofE. coli in dug well water from Celeban Tahunan of Yogyakarta City by conducting en experiment which followed pre test post test with control group design. The dose of the seed powder was 1,2 gram per liter processed water. The results show that the mean decrease of E. coli in the treatment group was1019,313 MPN/100 ml or about 73,245 %, meanwhile in the control group it was only 152,733 MPN/100 ml or about 20,324 %. Further analysis proved thatthe difference of the mean reduction was statistically significant (p < 0,001). It is implied that Kelor seed powder is potential for decreasing microbes in drinking water, and therefore people is advised to use it as one alternative for water purification.